Methane Number Control of Fuel Gas Supply System Using Combined Cascade/Feed-Forward Control - Soon-kyu Hwang; Byung-gun Jung (Journal of Marine Science and Engineering, 2020)
Liquefied natural gas began to attract attention as a ship fuel to reduce environmental pollution and increase energy efficiency. During this period, highly efficient internal combustion engines emerged as the new propulsion system instead of steam turbines. However, Otto-cycle engines must use fuel that meets the methane number that was given by the engine makers. The purpose of this study was to develop a system configuration and a control method of methane number adjustment using combined cascade/feed-forward controllers for marine Otto-cycle engines to improve reference tracking and the disturbance rejection. The main principle involves controlling the downstream gas temperature of the fuel gas supply system to meet the required methane number. Three controllers are used in the combined cascade/feed-forward control for adjusting the downstream of the gas temperature: the cascade loop has two controllers and the feed-forward has one controller. The two controllers in the cascade loop are designed with proportional–integral (PI) controllers. The remaining controller is based on feed-forward control theory. A simulation was conducted to verify the efficacy of the proposed method, focusing on the disturbance rejection and set-point tracking, in comparison with a single PI controller, a single PI controller with feed-forward, and cascade control.